An unsteady CFD modelling of a single slope solar still. (2021) - Mittal, Gaurav
Abstract: An unsteady CFD modelling of a single slope solar still is done using ANSYS Fluent. In the model, only the humid zone (air + water vapour mixture) is considered with specified temperatures at the bottom (water) and top (glass) level. The boundary conditions of temperature are specified for 24-hour duration, and the unsteady simulations are also conducted for 24-hour duration. Evaporation and condensation rates are derived based on water vapour mass fraction gradient at the evaporating (bottom) and condensing (top) surfaces. A number of User Defined Functions (UDFs) are used to implement this approach. The approach gives instantaneous as well as daily distillate output. The approach is computationally non-expensive and can help in evaluating the distillate output from a variety of configurations when temperatures at the bottom and top surfaces are known.